Sistem Pendeteksi Kecelakaan Pada Sepeda Motor Berdasarkan Kemiringan Menggunakan Sensor Gyroscope Berbasis Arduino - Aries Suprayogi; Hurriyatul Fitriyah; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Motorbikes are transportation that are generally in great demand by citizens of developed countries, especially Indonesia. With the increasing population and enthusiasts of motorbikes, the number of accidents in traffic will increase every year. The lack of handling of motorcycle accident sufferers at the time of the incident resulted in a high mortality rate. By knowing the slope of the motorcycle can be stated as an accident. Namely the slope of 10 ° - 50 ° for the left and the slope of 130 ° - 170 ° for the right. Therefore an accident detection system was built on a motorcycle based on the slope using a sensor gyroscope which was used to read the slope of the motorcycle, then sent a notification in the form of an SMS to the victim's family's cellphone via the GSM SIM900A Module. The MPU6050 sensor which is the reader of the slope value on the system installed on the motorbike will be processed on the Arduino Uno microcontroller. If the slope reading is stated as an accident, the GSM SIM900A Module will send a notification in the form of a help message to the relatives or families of the victims with the number that already exists on the GSM SIM900A module. By doing the slope alternately between left and right is selected with the roll value in the MPU6050 Sensor ranging ± -80.00- ± 50.00 expressed with an angle of 10 ° -50 ° and the slope value ± -20.00- ± 74.00 then expressed at an angle of 130 ° ¬ -170 ° the angles are expressed as the angle of the accident on the system and the boundary conditions are 60 ° -120 ° where the roll value is ± -21.00 - ± 1.00 which is declared as a normal system or does not send messages. The system will read the slope if it does not meet the boundary conditions of the roll angle, the system will immediately send a notification in the form of a message of assistance to relatives or victims' families with 80% accuracy if not constrained by the network / signal on the GSM SIM900A Module.